(untitled) (Ustozlar uchun, 2025)
This article discusses the methodology of using literary works in teaching English to university students. It highlights how literature enhances linguistic, communicative, and cultural competence by exposing learners to authentic language and real-life contexts. The paper explains pre-reading, while-reading, and post-reading strategies, as well as criteria for selecting appropriate texts. It also presents practical classroom activities that develop vocabulary, critical thinking, and creativity. The study concludes that literature is a valuable and effective tool for improving students’ English proficiency.